Student craft teachers’ garment-fitting process analysed using qualitative video analysis - Härkki Tellervo; Rönkkö Marja-Leena (Oslo and Akershus University College, Learning Centre and Library, 2025)
We studied student craft teachers’ garment-fitting activity as a demanding learning task that is indicative of students’ understanding of garment fit. Studying fit is essential in garment making. Simultaneously, fit is a complicated issue. As part of this clothing course, the students were given a form that listed areas to examine (bust, seams, darts etc.). They were instructed to think aloud, mark problematic areas and the placement of darts on a picture, and make written notes. While appreciating the potentially challenging social character of this peer-evaluation situation, this research aimed to understand how student craft teachers assess garment fit on a master’s-level clothing course. Two research questions were set: 1) What roles did the students take on during the fitting sessions? 2) How did the students assess garment fit? Eleven students provided their informed consent to participate and their video recordings of their fitting sessions. The study results are based on a qualitative content analysis of these participants’ videos. The results show that the students’ understanding of fit and the fitting activity was underdeveloped. Students missed or explained away even obvious fit issues (e.g., horizontal or vertical folds of fabric, horizontal or diagonal drag lines, bagging, overly long/short sleeves or bodices), and their discussions showed that a basic understanding of fitting-related vocabulary and technical structures was underdeveloped. Three different ways to handle fit issues were identified: through peer dialogue, independently and through confirmatory questions. We conclude with some future directions for refreshing the teaching of garment fitting in teacher education.